Coumarin-Chalcone Hybrids as Inhibitors of MAO-B: Biological Activity and In Silico Studies - Guillermo Moya-Alvarado; Osvaldo Yañez; Nicole Morales; Angélica González-González; Carlos Areche; Marco Tulio Núñez; Angélica Fierro; Olimpo García-Beltrán (Molecules, 2021)
Fourteen coumarin-derived compounds modified at the C3 carbon of coumarin with an α,β-unsaturated ketone were synthesized. These compounds may be designated as chalcocoumarins (3-cinnamoyl-2H-chromen-2-ones). Both chalcones and coumarins are recognized scaffolds in medicinal chemistry, showing diverse biological and pharmacological properties among which neuroprotective activities and multiple enzyme inhibition, including mitochondrial enzyme systems, stand out. The evaluation of monoamine oxidase B (MAO-B) inhibitors has aroused considerable interest as therapeutic agents for neurodegenerative diseases such as Parkinson’s. Of the fourteen chalcocumarins evaluated here against MAO-B, ChC4 showed the strongest activity in vitro, with IC50 = 0.76 ± 0.08 µM. Computational docking, molecular dynamics and MM/GBSA studies, confirm that ChC4 binds very stably to the active rMAO-B site, explaining the experimental inhibition data.